2019
DOI: 10.1002/14651858.cd013406
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for managing cognitive impairment after stroke

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:• To determine the effects of each type of psychological intervention for cognitive impairment (i.e. cognitive rehabilitation; cognitive training; psychological or behavioural interventions, or both) on cognitive outcomes for people with cognitive impairment after stroke compared with those of other non-pharmacological interventions, including usual care, non-specific activities, or other types of psychological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The thinking domain was also found to be at a moderate level. Persistent thinking problems may be caused by poststroke cognitive impairment, a common complication following a stroke, influencing survivors’ functional impairment and reducing HRQoL (Hickey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The thinking domain was also found to be at a moderate level. Persistent thinking problems may be caused by poststroke cognitive impairment, a common complication following a stroke, influencing survivors’ functional impairment and reducing HRQoL (Hickey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These interventions enhance cognitive abilities in deficit areas through repeated practice and challenging tasks that require problem-solving, pattern recognition, or memory exercises. The goal is to improve cognitive performance and transfer the gains to real-life situations [24]. Maier et al conducted a study to evaluate the effect of adaptive conjunctive cognitive training (ACCT) on four domains of cognition.…”
Section: Interventions and Future Directionsmentioning
confidence: 99%
“…They concluded that this method positively influenced spatial awareness and attention and improved depression in chronic post-stroke survivors [15]. Lastly, the behavioral intervention strategy concentrates on the survivors' ability to develop compensatory strategies by combining educational information and therapeutic techniques to achieve several goals that help individuals comprehend their cognitive strengths and weaknesses, ultimately enhancing their quality of life and psychological well-being [24]. Other non-pharmacological interventions for PSCI are music therapy, aerobic exercise, acupuncture, noninvasive brain stimulation, and caregiver education [25].…”
Section: Interventions and Future Directionsmentioning
confidence: 99%
“…A previous qualitative enquiry gathered the perspectives of key stakeholders on the design of a cognitive rehabilitation intervention post-stroke, focusing solely on psychological interventions [ 27 ]. This previous qualitative study was underpinned by a systematic review of non-randomised controlled studies of psychological interventions [ 28 ] and highlighted the need for improving confidence and self-efficacy in the management of cognitive impairment post-stroke, in addition to the importance of effective information provision on stroke sequalae and psychoeducation regarding the consequences of stroke [ 27 ]. In contrast to the qualitative enquiry of Merriman et al [ 27 ], the current study elicits perspectives on all types of non-pharmacological rehabilitation interventions, not only psychological interventions, for cognitive impairment post-stroke, as evidenced from our previous systematic review [ 26 ].…”
Section: Introductionmentioning
confidence: 99%